Body Ideas and Political Communities in Eric Voegelin's Early Work on Race - Morales, Bernat Torres; Muth, Nicoletta Scotti (Eric Voegelin Studies: Yearbook, 2024)
Eric Voegelin's "Rassenbücher", both published in Germany only a few months apart in the tumultuous year of 1933, had until recently received relatively limited attention. These works were often considered merely a youthful episode preceding Voegelin's American exile. However, this perception has dramatically changed in recent times. On the one hand, the systematic analysis carried out in these works has finally been acknowledged for its complexity and has been integrated into the larger, never-completed project of a "Theory of Government". The unconventional aims of this project remained pivotal to Voegelin's later work. On the other hand, the renewed importance of corporeality and the concept of race in contemporary political thought encourages a closer investigation of the role played by bodily ideas in the formation of political communities. This prompts the question of whether Voegelin's concepts can be applied to broader geographical and historical contexts. See Less